2016
DOI: 10.3354/dao03005
|View full text |Cite
|
Sign up to set email alerts
|

Survival behaviour and virulence of the fish pathogen Vibrio ordalii in seawater microcosms

Abstract: Vibrio ordalii, the causative agent of atypical vibriosis, is a Gram-negative, motile, rod-shaped bacterium that severely affects the salmonid aquaculture industry. V. ordalii has been biochemically, antigenically and genetically characterized. However, studies on the survival behaviour of this bacterium in aquatic environments are scarce, and there is no information regarding its disease transmission and infectious abilities outside of the fish host or regarding water as a possible reservoir. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In this study, the survival and morphology of non-O1/O139 V. cholerae cells were investigated under starvation conditions, and the results showed that non-O1/O139 V. cholerae could survive a long time of 6 months with reduction in the size of cells, turning them from rods to approximately spherical, which was consistent with the long-term survival and morphological changes of other Vibrio spp. ( 15 , 16 ). It is clear that bacteria have evolved mechanisms to survive under starvation stress by reducing cell size and turning into a round cell shape ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the survival and morphology of non-O1/O139 V. cholerae cells were investigated under starvation conditions, and the results showed that non-O1/O139 V. cholerae could survive a long time of 6 months with reduction in the size of cells, turning them from rods to approximately spherical, which was consistent with the long-term survival and morphological changes of other Vibrio spp. ( 15 , 16 ). It is clear that bacteria have evolved mechanisms to survive under starvation stress by reducing cell size and turning into a round cell shape ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three V. ordalii strains were used: The type strain ATCC 33509 T and two strains, Vo-LM-13 and Vo-LM-18, previously isolated from vibriosis outbreaks in Atlantic salmon cultured in Chile [3,6]. All were confirmed as V. ordalii according to the PCR protocol previously described [30].…”
Section: Methodsmentioning
confidence: 99%
“…While its pathogenicity is not correlated to erythrocytes hemagglutination capacity or biofilm formation in Atlantic salmon ( Salmo salar ), the hydrophobic properties of V. ordalii cells could play a role in virulence. Moreover, V. ordalii can evade the host immune system and can survive within Atlantic salmon mucus, which likely facilitates colonization [3,6]. However, many aspects of its ability to colonize and multiply within the fish hosts remain unclear.…”
Section: Introductionmentioning
confidence: 99%